2012
DOI: 10.4161/hv.20707
|View full text |Cite
|
Sign up to set email alerts
|

TLR9-adjuvanted pneumococcal conjugate vaccine induces antibody-independent memory responses in HIV-infected adults

Abstract: HIV-patients have excess of pneumococcal infection. We immunized 40 HIV-patients twice with pneumococcal conjugate vaccine (Prevnar, Pfizer) +/− a TLR9 agonist (CPG 7909). Peripheral blood mononuclear cells were stimulated with pneumococcal polysaccharides and cytokine concentrations measured. The CPG 7909 adjuvant group had significantly higher relative cytokine responses than the placebo group for IL-1β, IL-2R, IL-6, IFN-γ and MIP-β, which, did not correlate with IgG antibody responses. These findings sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In the same cohort of patients, increased Ab dependent cellular immunity was detected after the second vaccination accompanied by significantly higher PBMC cytokine responses involving IL-1 ( p = 0.0046), IL-6 ( p = 0.0051), IFN-α ( p = 0.0047), MIP-β ( p = 0.0086), and IL-2R ( p = 0.0062). PBMC from the CpG 7909 adjuvanted group responded to LPS stimulation by producing IL-1β ( p = 0.038) and IFN-α ( p = 0.019) at significantly higher levels when compared to non-CpG controls [94]. HIV pro-viral DNA levels fell by 12.6% in the CpG 7909 treated group versus a rise of 6.7% in the placebo group after the 3rd vaccination (at 10 months) ( p = 0.056).…”
Section: Cpg Odn As An Adjuvant In Hiv-infected Individualsmentioning
confidence: 99%
“…In the same cohort of patients, increased Ab dependent cellular immunity was detected after the second vaccination accompanied by significantly higher PBMC cytokine responses involving IL-1 ( p = 0.0046), IL-6 ( p = 0.0051), IFN-α ( p = 0.0047), MIP-β ( p = 0.0086), and IL-2R ( p = 0.0062). PBMC from the CpG 7909 adjuvanted group responded to LPS stimulation by producing IL-1β ( p = 0.038) and IFN-α ( p = 0.019) at significantly higher levels when compared to non-CpG controls [94]. HIV pro-viral DNA levels fell by 12.6% in the CpG 7909 treated group versus a rise of 6.7% in the placebo group after the 3rd vaccination (at 10 months) ( p = 0.056).…”
Section: Cpg Odn As An Adjuvant In Hiv-infected Individualsmentioning
confidence: 99%
“…However, as we were unable to assess changes in residual viremia or viral transcription, it remains uncertain whether the decrease in proviral reservoir observed in this study can be attributed to induced virus production in latently infected cells, effects on HIV-specific T cell immunity, or non-specific effect on other immune effector cells, or a combination of the three. It has previously been shown that besides increasing antibody production, CPG 7909-adjuvanted pneumococcal vaccination also enhances antibody-independent cellular immunity [29]. In addition to B cells, TLR9 is also abundant in plasmacytoid dendritic cells (pDCs) [41].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their immune stimulatory properties via TLR9, synthetic CpG oligodeoxynucleotides (CpG ODNs) are used as vaccine adjuvants and have been shown to enhance vaccine immunogenicity in HIV-infected individuals and healthy adults with an acceptable safety profile [25][28]. Besides inducing humoral immunity, CPG-adjuvanted pneumococcal vaccine has been shown to enhance antibody-independent cellular immunity [29], [30]. In addition, CpG ODNs reactivate HIV-1 expression in latently infected cells by mechanisms that involve TLR9 signalling and eventually activation of NF-κB [31], [32], but the mechanistic details remain largely unresolved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a post hoc analysis of a phase I study, ART suppressed HIV-infected individuals who received a pneumococcal vaccine regimen plus CPG 7909 had a reduction in proviral DNA compared to the group that received the vaccine with placebo. Reductions in proviral DNA was correlated with increasing levels of HIV specific CD8 cells [98, 99]. …”
Section: Intracellular Reservoir Targetsmentioning
confidence: 99%